2019
DOI: 10.1039/c9tc00805e
|View full text |Cite
|
Sign up to set email alerts
|

Ancillary ligand-assisted robust deep-red emission in iridium(iii) complexes for solution-processable phosphorescent OLEDs

Abstract: Two different kinds of ancillary ligands such as picolinate and thenoyltrifluoroacetylacetonate have profound effects on the excited state properties of deep red emissive iridium(iii) complexes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 80 publications
0
28
0
Order By: Relevance
“…Among the various metal sulfides, iron sulfides have proven to be appealing to SIBs, owing to their high theoretical capacity (≈610 mAh g −1 for FeS), natural abundance and low toxicity. However, they also show inferior electrochemical properties owing to their sluggish kinetics and severe volume changes during repeated cycling …”
Section: Introductionmentioning
confidence: 99%
“…Among the various metal sulfides, iron sulfides have proven to be appealing to SIBs, owing to their high theoretical capacity (≈610 mAh g −1 for FeS), natural abundance and low toxicity. However, they also show inferior electrochemical properties owing to their sluggish kinetics and severe volume changes during repeated cycling …”
Section: Introductionmentioning
confidence: 99%
“…Another effective strategy is the use of hollow and/or porous MoSe 2 ‐based electrode materials. The empty space in such structures could shorten the diffusion length of Na + and accommodate the mechanical stress upon cycling, thereby improving the cycling stability and rate capability . In particular, a 1 D tubular structure, regarded as a unique hollow structure, is favorable for electron/ion transport and contact between electrode and electrolyte owing to an enhanced surface‐to‐volume ratio and short transport length …”
Section: Introductionmentioning
confidence: 69%
“…Three peaks in the Mo 3d spectrum at 229.1, 230.6, and 232.2 eV were assigned to Mo 3d 5/2 , Se 3s, and Mo 3d 3/2 , respectively (Figure c). The peak position for Mo 3d 3/2 and Mo 3d 5/2 suggested an oxidation state of Mo 4+ , verifying the formation of MoSe 2 . The Se 3d spectrum could be deconvoluted into three different peaks at 54.6, 55.5, and 56.4 eV, representing Se 3d 5/2 , Se 3d 3/2 , and Se−Se, respectively (Figure d) .…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al. used NaCl as a washable template to produce metal sulfide/carbon microspheres with cubic nanorooms (MeS x /C‐NR; Figure a) . The authors reported that this method can be generalized for the synthesis of any metal sulfide/carbon composites, such as MoS 2 /C‐NR, SnS/C‐NR, and FeS 2 /C‐NR (Figure b–h).…”
Section: Synthesis Of Metal Chalcogenide Materials By Aerosol‐assistementioning
confidence: 99%
“…g) TEM and h) elemental mapping images of FeS 2 /C‐NR. Reproduced with permission . Copyright 2019, Royal Society of Chemistry.…”
Section: Synthesis Of Metal Chalcogenide Materials By Aerosol‐assistementioning
confidence: 99%